Comprehensive genomic profiling of primary bladder mucinous adenocarcinoma, a rare genitourinary cancer: A case report - Shinkuro Yamamoto; Shingo Ashida; Tomoya Nao; Kaho Murakami; Ryohei Iga; Tsutomu Shimamoto; Hideo Fukuhara; Nobutaka Shimizu; Satoshi Fukata; Atsushi Kurabayashi; Takashi Karashima; Keiji Inoue (Urology Case Reports)
Primary bladder mucinous adenocarcinoma is a rare genitourinary cancer. Here, we present the case of a 75-year-old woman where pathological and imaging findings led to the diagnosis of primary bladder mucinous adenocarcinoma. She underwent treatment with paclitaxel–ifosfamide–cisplatin (TIP). After two cycles of TIP therapy, FoundationOne CDx, a comprehensive genomic profiling test, was performed, revealing variants in ATM, SMAD4, BRD4, and NOTCH3. These genomic profiling test results may lead to the development of novel therapeutic agents for primary bladder mucinous adenocarcinoma.